Experimental dSPACE Analysis for Self-excited Induction Generator Used in Voltage Control - Rachid El Akhrif; Ahmed Abbou; Mohamed Barara; Mohamed Akherraz; Youssef Majdoub (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
In this paper, a new approach is proposed for keeping the RMS voltage output constant, the system is supplying by a self-excited induction generator (SEIG) driven by a controlled DC motor with variable speed and load. The scheme used in this paper is based on a classical Proportional-Integral regulator wich controls a SPWM switching. A MATLAB Simulink model of the system is developed to maintain the AC voltage at the desired value. Then a comparison is examined between simulation and experimental results using dSPACE board. The results are provided to verify the effectiveness of this approach and it gives very high performance.